A copper oxide nanorod derived metal–organic framework nanocomposite: a robust and sensitive electrocatalyst for the detection of furazolidone. (7th December 2022) - Salandari-Jolge, Naeime; Ensafi, Ali A.; Rezaei, Behzad
Abstract : A voltammetric sensor based on a ZIF-8@CuO nanorod-modified GCE was developed to determine selectively furazolidone by differential pulse voltammetry. Abstract : In this work, a voltammetric sensor based on a ZIF-8@CuO nanorod-modified glassy carbon electrode (GCE) was developed to selectively determine furazolidone (FUZ) by differential pulse voltammetry (DPV). For this purpose, copper oxide (CuO) nanorods were synthesized. Then, cobalt nanoparticles were synthesized on the bed of CuO nanorods uniformly. Finally, Zeolitic Imidazolate Framework-67 (ZIF-67) nanoparticles were grown on predetermined sites of cobalt nanoparticles. The growth of ZIF-67 on the active cobalt sites leads to formation of single and controlled ZIF-8 nanoparticles. CuO@ZIF-8 nanorods were characterized using various techniques in different stages of synthesis. It was shown that the high conductivity of CuO nanorods provides fast electron transfer on the sensor surface, and ZIF-67 increases the absorption of FUZ on the electrode surface. Under optimal conditions, the linear range of the method was calculated to be 8.0 × 10 −9 mol L −1 –6.0 × 10 −6 mol L −1 for furazolidone, with a detection limit of 2.3 × 10 −9 mol L −1 . Then, the sensor was used to determine the concentration of FUZ in different plasma samples, and the recovery percentages ranged from 96.0% to 102.4%. Also, the proposed electrochemical sensor has advantages such as low cost, high speed, high sensitivity and selectivity, and a wide linear range.